Design of Injection Mould for Washing Machine Based on CAE Analysis - Quan, Wang; Min, Zhang (Recent Patents on Materials Science, 2017)
Background: Injection mould has become an important industry. The traditional method of optimizing a product through artificial experience has been unable to meet the needs of the market. Moldflow can be used for defect analysis before injection molding. Objective: The external barrel of washing machine of injection process analysis was presented by Moldflow. Methods: Molding process of the external barrel of washing machine was analyzed under two kinds of gates and cooling channels by Moldflow. The differences between the two designs are compared, such as air traps, welt line, warping and mould temperature by Moldflow analysis. Results and Conclusion: The paper reviews various patents of injection mould for washing machine in the recent years, such as washing machine design, materials and structure. The reasonable molding process conditions were assessed and the design was obtained. The quality of a part can be promoted maximally, reducing the molding period. The results show that the CAE analysis has a strong guiding effect on the molding process.
Keywords: Moldflow analysis